Laser speckle contrast imaging with extended depth of field for in-vivo tissue imaging - Sigal, Iliya (Optical Society of America, 2013)
This work presents, to our knowledge, the first demonstration of the Laser Speckle Contrast Imaging (LSCI) technique with extended depth of field (DOF). We employ wavefront coding on the detected beam to gain quantitative information on flow speeds through a DOF extended two-fold compared to the traditional system. We characterize the system in-vitro using controlled microfluidic experiments, and apply it in-vivo to imaging the somatosensory cortex of a rat, showing improved ability to image flow in a larger number of vessels simultaneously.